Getting It Right–Creating a Wildlife Rehabilitation Center from Scratch - Parker, Kip (Wildlife Rehabilitation Bulletin, 2005)
This article is based on a presentation made in 1998 at the 16th annual National Wildlife Rehabilitators Association Annual Symposium in Seattle, Washington. The original presentation was followed in 2000 with another more detailed presentation and publication (Parker 2000). The reader is urged to read this reference, and other suggested reading, fully, before undertaking the creation or operation of a wildlife rehabilitation center or program.